2008
DOI: 10.1021/jm8003653
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-Chloro-N-(4-methoxyphenyl)-N-methylquinazolin-4-amine (EP128265, MPI-0441138) as a Potent Inducer of Apoptosis with High In Vivo Activity

Abstract: Using a live cell, high-throughput caspase-3 activator assay, we have identified a novel series of 4-anilinoquinazolines as inducers of apoptosis. In this report, we discuss the discovery of 2-chloro-N-(4-methoxyphenyl)-N-methylquinazolin-4-amine, compound 2b (EP128265, MPI-0441138) as a highly active inducer of apoptosis (EC50 for caspase activation of 2 nM) and as a potent inhibitor of cell proliferation (GI50 of 2 nM) in T47D cells. Compound 2b inhibited tubulin polymerization, was effective in cells overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…10 Because this chemotype is quite unexplored as a class of tubulin inhibitors, we initiated a molecular modeling study with the goal of rationalizing the pivotal pharmacophore features required to achieve dual inhibition of tubulin polymerization and TKs. Some attempts to draw a common SAR were previously published, 10,11 but these were aimed mainly at determining differences between the requirements of the two targets.…”
Section: Resultsmentioning
confidence: 99%
“…10 Because this chemotype is quite unexplored as a class of tubulin inhibitors, we initiated a molecular modeling study with the goal of rationalizing the pivotal pharmacophore features required to achieve dual inhibition of tubulin polymerization and TKs. Some attempts to draw a common SAR were previously published, 10,11 but these were aimed mainly at determining differences between the requirements of the two targets.…”
Section: Resultsmentioning
confidence: 99%
“…Many research groups have proved that the overexpression of Aurora-A induces several cancerassociated phenotypes, including enhanced cell proliferation and colony formation, and inhibition of apoptosis [39][40][41]. Some quinazoline derivatives interact with tubulin [42] and interfere with its polymerization, others act by modulating Aurora kinase activity [43][44] or have an effect in critical phases in the cell cycle [45] or act as apoptosis inducers [46][47]. Similarly compound 2 was also docked with active site of Aurora kinase inhibitor (pdb ID 2WTV (Figure 8b).…”
Section: Aurora Kinase Assay Studiesmentioning
confidence: 99%
“…Nowadays many novel agents to activate and promote apoptosis in cancer cells via targeting regulators of apoptosis are being explored [98]. Some studies have reported structure activity relationship (SAR) on 4-anilinoquinazolines as potent apoptosis inducers and identified anticancer development candidate 66, which displayed in vivo anticancer activity and high BBB penetration [99]. To optimize this class of anticancer agents, the 2-Cl group in 66, a potential liability due to its chemical reactivity, is replaced by other functional groups.…”
Section: Apoptosis Inducersmentioning
confidence: 99%